2014
DOI: 10.1002/tox.21988
|View full text |Cite
|
Sign up to set email alerts
|

Use of histopathology and elemental accumulation in different organs of two benthophagous fish species as indicators of river pollution

Abstract: The bottom feeding fish species have a good potential to be used for assessments of pollution, as they are under pressure from pollutants from both water and sediments. In this study, the level of similarity of histopathological responses to pollution in gills and liver between barbel (Barbus barbus) and sterlet (Acipenser ruthenus) from the Danube River was assessed, and compared with elemental concentrations in their gills, liver, and muscle. Results indicate that the detected metal concentrations were likel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 30 publications
2
20
0
Order By: Relevance
“…Thus these biomarkers are often suitable as a rapid method for the detection of both acute and chronic effects of toxins and irritants in various tissues [104]. Histopathological alterations of various fish organs have a pronounced value in aquatic toxicology [105] and they are widely used in monitoring of aquatic pollution [101,102,104,[106][107][108][109].…”
Section: Biomarkersmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus these biomarkers are often suitable as a rapid method for the detection of both acute and chronic effects of toxins and irritants in various tissues [104]. Histopathological alterations of various fish organs have a pronounced value in aquatic toxicology [105] and they are widely used in monitoring of aquatic pollution [101,102,104,[106][107][108][109].…”
Section: Biomarkersmentioning
confidence: 99%
“…Their large surface area, direct contact with water, multiple important functions, and delicate structure make them suitable markers for environmental pollution [104, 108,109,155]. Tilapia orally exposed to 60 µg MC-LR/fish/day for 21 days [112] displayed hyperaemia and epithelium lifting.…”
Section: Gillsmentioning
confidence: 99%
“…That procedure has been widely accepted and applied for histopathology-based evaluation of water pollution (Liebel et al 2013;Lujić et al 2015;Rašković et al 2015). Since chemical and microbiological water quality of three rivers in north-eastern Macedonia which were selected for this study, Bregalnica, Zletovska and Kriva, was determined simultaneously with chub sampling (Ramani et al 2014), we were able to associate observed histopathological alterations to specific degrees and types of water contamination.…”
Section: Introductionmentioning
confidence: 99%
“…The importance of such approach is supported by the fact that recently several other field surveys of contamination of aquatic ecosystems, which were based on gill histopathology, have been performed in different regions in the world: in Egypt, using Nile catfish (Clarias gariepinus; Authman et al 2013), in Pakistan, using Mozambique tilapia (Oreochromis mossambicus; Jabeen and Chaudhry 2013), in Brasil, using fish species Astyanax aff. fasciatus and Nile tilapia (Oreochromis niloticus; Liebel et al 2013), and in Serbia, using pike (Esox lucius), zander (Sander lucioperca) and Wels catfish (Silurus glanis; Lujić et al 2015), as well as barbel (Barbus barbus) and sterlet (Acipenser ruthenus; Rašković et al 2015). Since our study was conducted in two periods, spring and autumn of 2012, which differed concerning fish physiology and physico-chemical characteristic of the river water, seasonal variations of histopathological alterations on Vardar chub gills were also assessed.…”
Section: Introductionmentioning
confidence: 99%
“…Histopathology (HP) is commonly used as a marker in polluted freshwater ecosystems (Triebskorn, Telcean, Casper, Farkas, Sandu, Stan, Colărescu, Dori & Köhler ; van Dyk, Cochrane & Wagenaar ; Madureira, Rocha, Cruzeiro, Rodrigues, Monteiro & Rocha ; Lujić, Matavulj, Poleksić, Rašković, Marinović, Kostić & Miljanović ; Rašković, Poleksić, Višnjić‐Jeftić, Skorić, Gačić, Djikanović, Jarić & Lenhardt ), but is rarely used as indicator of the health status of fish produced in aquaculture systems. Recently, studies were published confirming that HP is a useful indicator of fish health in earthen ponds.…”
Section: Introductionmentioning
confidence: 99%